From Stained to Stunning: A Case Report on Smile Makeover - Singh, Rajeev; Mistry, Gaurang; Parab, Sheetal; Choudhary, Manju; Pokharkar, Amit; Shah, Saloni (Journal of Neonatal Surgery, 2025)
Smile is an integral part of a person’s appearance, and it serves as a gateway to the world. Various dental concerns, such as stains and open embrasures, can affect the aesthetic and functional value of the teeth, which in turn causes disharmony of the perfect smile. Patient with such concerns feel insecure, conscious, and dissatisfied with their appearance. This case highlights the transformation of unesthetic teeth through meticulous planning and precise treatment execution, showcasing the power of a comprehensive approach in achieving a beautiful and confident smile.